Cutting balloon to treat post-stenting intramural hematoma during ST elevation myocardial infarction - Servoz, Clément; Monségu, Jacques; Abdellaoui, Mohamed; Faurie, Benjamin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
A 71-year-old woman was admitted to our institution for an ongoing inferior ST-elevation myocardial infarction (STEMI). TIMI 3 flow of a mid-right coronary artery (RCA) thrombotic occlusion was restituted with balloon angioplasty (Sapphire II NC 3 × 15 mm, OrbusNech) and stenting at 9 atm (Ultimaster Tansei 3.5 × 28 mm, TERUMO) (Figure 1 A). Post-stenting angiogram revealed a distal stent edge stenosis which was not restituted after intracoronary nitroglycerin excluding vasospasm (Figure 1 B). Moreover, this lesion was evolutive: the stenosis aspect and degree became worse. As the dissection mechanism was suspected, we treated this lesion with a second stent. While stenting, we observed a distal migration of the sub-intimal contrast dye that made us think about a probable iatrogenic hematoma extension. A tight distal RCA stenosis was revealed on angiogram with clear subintimal dye trapping and extraluminal compression while the patient had recurrence of chest pain and inferior ST-segment elevation (Figure 1 C).